(untitled) (Research, Society and Development, 2020)
For a strategic tourism planning of a location, making a diagnosis of the situation of a location is a fundamental task before planning. Therefore, the objective of the research was to analyze the tourist activity of Aquidauana through the SWOT matrix. For this, the SWOT analysis was applied in the municipality of Aquidauana based on the view of the agents involved with tourism in the municipality. The methodology used in the study was recommended for the localities by (Haider, Kotler, Rein, & Gertner, 2006). Qualitative research was carried out, based on primary data from five in-depth interviews with the public manager, businesswoman, and specialists in the local tourist trade, which made it possible to identify the relevant variables on the main strengths, weaknesses, opportunities, and threats of the place. A map was created with the geographical location and the characterization of the study area. The main contribution of the research was to have produced a reliable diagnosis regarding the tourist activity of Aquidauana. The academic relevance of the study consists in the application of the SWOT analysis method in the tourist environment of the city, the methodology had not been used regardind the tourist environment of Aquidauana. It is concluded that there are significant barriers related to basic and tourist infrastructures, qualified labor, public, and social policies for the development of tourism in the municipality; however touristic opportunities and potential of the region were evidenced. The article limits itself by applying a single methodological tool, in this sense for future research it is suggested to use the content analysis in interviews of social actors of the tourism of Aquidauana to generate more relevant results.